Experimental determination of the elbow's center of rotation using the VICON™ optoelectronic motion capture system. - Guerre, Elvire; Laronde, Pascale; Cussonneau, Jérôme; Fontaine, Christian; Wavreille, Guillaume (Surgical & Radiologic Anatomy, 2016)
Purpose: Knowledge of elbow kinematics is essential to better understand this joint. There is currently no reliable dynamic method to accurately study the elbow joint in a non-invasive manner. The goal of this study was to implement an accurate protocol to study in vivo elbow kinematics using a VICON™ optoelectronic motion analysis system. Méthods: The elbow's centers of rotation (CR) were calculated for 10 anatomical specimens. The effect of skin movement was determined by comparing measurements taken using skin surface markers and bone-fixed markers. The validated protocol was then used in 30 healthy subjects who underwent passive elbow joint movements. Results: The elbow's CR was found to be distal (7 ± 14 mm), lateral (4 ± 9 mm) and anterior (4 ± 10 mm) to the medial epicondyle in vitro. Mean CR values for anatomical specimens did not differ whether calculated using the skin-based or bone-fixed markers. Conclusion: This study has validated a dynamic, non-invasive, and accurate method for locating the elbow's center of rotation. This preliminary study thus found a different center of rotation of the one in the middle of the trochlea previously thought. This could lead us to reflect on the designs of our prostheses to reduce the mechanical stresses and the risk of loosening.